Vpliv spola in spolnih hormonov na nastanek akutnih ishemičnih poškodb pri izoliranem podganjem srcu - Andjelkovič, Lea (Medicinski razgledi, 2004)
Sex might be an important factor in the development of certain ischemic diseases of the heart. We tried to assess the effects of treating rats with estradiol or testosterone on the development of myocardial damage caused by ischemia/reperfusion. Experiments were carried out on the isolated hearts of sexually mature rats of both sexes (230-330 g) which were perfused with aerated Krebs-Henseleit solution for 30 minutes and then subjected to 40 minutes zero-flow ischemia followed by 55 minutes of reperfusion. The severityof myocardial damage was assessed based on postischemic changes in thefollowing registered parameters: coronary blood flow, lactate dehydrogenaserelease rate, left ventricular pressure, heart rate and duration of ventricular fibrillation during reperfusion. The coronary flow was higher in the hearts of rats treated with estradiol or testosterone than in those from the control groups. Postischemic LDH values were elevated in all groups, but the highest values were observed in the postgravid group. Postischemic heart rate values were lower than before ischemia. The highest values were observed in the postgravid group. In our experiment a protective role of sex hormones regarding development of ischemic/reperfusion damage in isolated rat hearts has been shown.
Keywords: Laktatna dehidrogenaza; Myocardial Reperfusion Injury; Miokardna kontrakcija; Estradiol; Miokardna, reperfuzijska poškodba; Testosterone; Testosteron; Lactate Dehydrogenase; Myocardial Contraction; Koronarni obtok; Podgane; Heart Rate; Prekatna fibrilacija; Coronary Circulation; Spolni faktorji; Ventricular Fibrillation; Srčna frekvenca; Sex Factors; Rats; heart; srce; ishemija; spol